2009
DOI: 10.1590/s0102-33062009000200012
|View full text |Cite
|
Sign up to set email alerts
|

Compostos secundários durante a decomposição foliar de espécies arbóreas em um riacho do sul do Brasil

Abstract: RESUMO -(Compostos secundários durante a decomposição foliar de espécies arbóreas em um riacho do sul do Brasil). Os objetivos deste trabalho foram identificar os compostos secundários e avaliar o comportamento destes em folhas de Sebastiania commersoniana (Baill.) Smith e Downs e Eucalyptus grandis Hill ex Maiden durante diferentes estágios de decomposição em um riacho de primeira ordem do norte do Rio Grande do Sul. Foram incubadas no riacho folhas das duas espécies, sendo essas retiradas do corpo hídrico ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
2
5
1
6
Order By: Relevance
“…Although eucalyptus leaves are usually considered relatively refractory to breakdown due to the high concentrations of secondary compounds and toughness and to the relatively low nutrient contents (e.g., Graça et al, 2002), the vegetation of the Cerrado biome is even tougher and more recalcitrant to biological breakdown (Moretti el al., 2007a). The breakdown rates of eucalyptus obtained in this study were faster than breakdown rates obtained in other studies with leaves of E. grandis (Gonçalves Jr., 2005;Hepp et al, 2009) in Brazilian streams. But these faster breakdown rates were probably more related to the characteristics of the stream rather than to the characteristics of the leaf species, which are similar (Gonçalves Jr., 2005;Moretti, 2009).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Although eucalyptus leaves are usually considered relatively refractory to breakdown due to the high concentrations of secondary compounds and toughness and to the relatively low nutrient contents (e.g., Graça et al, 2002), the vegetation of the Cerrado biome is even tougher and more recalcitrant to biological breakdown (Moretti el al., 2007a). The breakdown rates of eucalyptus obtained in this study were faster than breakdown rates obtained in other studies with leaves of E. grandis (Gonçalves Jr., 2005;Hepp et al, 2009) in Brazilian streams. But these faster breakdown rates were probably more related to the characteristics of the stream rather than to the characteristics of the leaf species, which are similar (Gonçalves Jr., 2005;Moretti, 2009).…”
Section: Discussioncontrasting
confidence: 60%
“…Abelho and Graça, 1996;Canhoto and Graça, 1996;Graça et al, 2002), where eucalyptus is also an introduced species, have shown that species of eucalyptus decompose relatively slow in comparison to the natural leaf litter in these streams. Although very few data is available on the decomposition rate of eucalyptus in Brazilian streams, the results obtained by Hepp et al (2009) andGonçalves Jr. (2005) for Eucalyptus grandis (0.0050 to 0.0068 day -1 ) are within the higher range reported (Gonçalves Jr., 2005;Moretti et al, 2007a, b) for breakdown rates of natural vegetation of the Cerrado in several Southeastern Brazilian streams (0.0019 to 0.0063 day -1 ). The main objective of this study was to assess whether nutrient availability may limit the process of leaf decomposition in a mountain stream located at the southern end of the Espinhaço Range Mountain, and, if so, whether macroinvertebrates, microorganisms, or both, mediate the effect.…”
Section: Introductionsupporting
confidence: 67%
“…The intrinsic characteristics and the stage of decomposition of leaf litter determine its quality for consumers [ 28 ]. Therefore, the contents of lignin, cellulose, nutrients, and secondary compounds as well as microbial colonization influence leaf quality [ 29 31 ]. It is well known that invertebrate shredders exhibit a feeding preference for high-quality leaves, i.e., with high nutrient contents and low amounts of structural compounds [ 27 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both species lost more than 50% of their secondary compounds during the first week of incubation in the stream. Previous studies have suggested that high concentrations of these compounds inhibit colonisation by invertebrates, slowing leaf breakdown (Hepp et al, 2009;Stout, 1989;Wantzen et al, 2002). However, the rapid leaching of these leaf compounds may have reduced the inhibitory effect on invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf chemical characteristics known to increase breakdown rates and nutritional quality of leaves for invertebrates in streams included high N and P (Ardón et al, 2009), low C:N ratio (Enríquez et al, 1993), secondary compounds (Hepp et al, 2009) and lignin content (Ardón et al, 2009). In contrast to the existing information from temperate streams, high diversity of tree species in the tropical riparian vegetation has prompted suggestions that leaf quality plays a more important role on decomposition than in temperate streams (Wantzen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%